Differential protein expression in exosomal samples taken from trauma patients. Issue 9 (10th July 2017) - Moyron, Ron B.; Gonda, Amber; Selleck, Matthew J.; Luo‐Owen, Xian; Catalano, Richard D; O'Callahan, Thomas; Garberoglio, Carlos; Turay, David; Wall, Nathan R.
Abstract: Traumatic brain injuries (TBI) are among the most misdiagnosed and underreported types of head trauma. The potential long‐term impact of undiagnosed or incorrectly identified concussions and other head injuries are potentially devastating, as evidenced by the increasing societal burden exhibited by soldiers returning from combat and athletes in contact sports. Concussions and TBI are notoriously difficult to correctly diagnose and prognosis for these injuries is poorly understood. In order to increase the likelihood of successful diagnosis, treatment, and prediction of outcomes, a definitive differential diagnosis will need to be established. The establishment of a "trauma–specific profile" or a panel of known trauma markers will significantly aid in this goal. Small membrane vesicles called exosomes have been shown to contain proteins and injury‐specific biomarkers. In the future it is possible that they could become an important tool, utilized for their diagnostic and therapeutic potential.